2013
DOI: 10.1159/000353099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Related to Late Recurrence - Later than 10 Years after the Initial Treatment - in Primary Breast Cancer

Abstract: Background: Breast cancer is associated with a relatively good prognosis. Prognostic factors examined to date are related to early recurrence while those related to late recurrence and their countermeasures remain unclear. Therefore, we examined the factors related to late recurrence. Patients and Methods: From January 1980 to August 2012, 4,774 patients who underwent primary treatment and estrogen (ER) and progesterone receptor (PgR) assessment were enrolled in this study. The patients were divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9,355 publications
(48 citation statements)
references
References 72 publications
2
42
0
4
Order By: Relevance
“…In our institute, we adopted the cut-off points 20% and 50%, as previous studies revealed that they were instrumental as reliable points. Moreover, the median value was 20% in all the primary cases and 50% in the cases with the TN type (8,20,21).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our institute, we adopted the cut-off points 20% and 50%, as previous studies revealed that they were instrumental as reliable points. Moreover, the median value was 20% in all the primary cases and 50% in the cases with the TN type (8,20,21).…”
Section: Discussionmentioning
confidence: 91%
“…Ibrahim et al (24) reported that patients with a Ki-67 index value of <20% exhibited a significantly higher post-recurrence survival compared to patients with a Ki-67 index value of ≥20%. Moreover, the bone, lung/pleura and chest wall were common sites of recurrence in the early recurrence group with highly proliferative tumors and liver metastasis was identified in 13.6% of the patients (21). In the late recurrence group exhibiting low proliferation, recurrence was more common in the lung/pleura and bone; however, liver and brain metastases were rarely encountered.…”
Section: Discussionmentioning
confidence: 93%
“…No one dropped out the NAC due to loss of follow-up or weak treatment compliance. There were dose reductions and/or delays for 52 women by neuropathic (37) and emetic (9) toxicity, surgery anticipation (4), or no clinical response (2). Dose reduction by only 20% (43) and/or one cycle (4) was the majority and therefore without influencing the overall efficacy of NAC.…”
Section: Variables and Treatmentmentioning
confidence: 99%
“…It presents heterogeneous molecular characteristics with great biological diversity and variable clinical outcomes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment decisions after initial diagnosis of HR breast cancer is determined by clinicopathological features and include presence of pathologically involved lymph nodes, large tumor size, high tumor grade, lymphovascular invasion, and/or high risk of recurrence based on a genomic assay (e.g., Recurrence Score [RS] >31 on the 21-gene recurrence assay) [22][23][24]. For patients who have completed treatment, studies have identified that a gene signature can be utilized to stratify risk of late distant metastases (>5-15 years).…”
Section: Discussionmentioning
confidence: 99%